Global Proteomic Analyses Reveals Abnormal Immune Regulation in Patients With New Onset Ankylosing Spondylitis - Yu, Zongchao; Hong, Xiaoping; Zhang, Xiaoli; Zheng, Fengping; Liu, Fanna; Xu, Huixuan; Zhu, Chengxin; Cai, Wanxia; Liu, Dongzhou; Yin, Lianghong; Hu, Bo; Tang, Donge; et al. (Frontiers in Immunology, 2022)
Background. Ankylosing spondylitis (AS) is a chronic inflammatory disease that can cause significant complications and is associated with high morbidity and mortality,In our previous work, we reveal the key features of proteins in new-onset ankylosing spondylitis patients Methods. Ankylosing spondylitis (AS) is a chronic inflammatory disease, and inflammation plays an essential role in AS pathogenesis. However, the complexity of the inflammatory process in AS is still poorly understood. Systematic proteomic and phosphorylation analyses of peripheral blood mononuclear cells (PBMCs) were applied to reveal potential pathways involved in AS pathogenesis. Results. Liquid chromatography-tandem mass spectrometry (LC–MS/MS) analysis was performed and discovered 782 differentially expressed proteins (DEPs) and 122 differentially phosphorylated proteins (DPPs) between 9 new-onset AS patients and 9 healthy controls. The DEPs were further verified using parallel reaction monitoring (PRM) analysis. PRM analysis verified that 3 proteins (HSP90AB1, HSP90AA1 and HSPA8) in the antigen processing and presentation pathway, 6 proteins (including ITPR1, MYLK and STIM1) in the platelet activation pathway and 10 proteins (including MYL12A, MYL9 and ROCK2) in the leukocyte transendothelial migration pathway were highly expressed in the PBMCs of AS patients. Conclusions. The key proteins involved in antigen processing and presentation, platelet activation and leukocyte transendothelial migration revealed abnormal immune regulation in patients with new-onset AS. These proteins may further help reveal the pathogenesis of AS and serve as candidate markers for AS diagnosis and new treatment targets.